Design and Development of Arabic Language Style for the Needs of Beginner-Level Speaking Proficiency Materials - Saleh, Sriwahyuningsih R.; sholihah, Atik; Hula, Ibnu Rawandhy N.; Doni, Chaterina Putri (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This research aims to develop Arabic language texts designed to improve beginner-level speaking proficiency for learners who are just starting to learn Arabic. This development is necessary because many existing teaching materials primarily provide information without fostering learners’ interactive engagement in the learning process. Moreover, numerous teachers still rely on conventional textbooks that inadequately support the enhancement of learners’ maharatul kalam (speaking skills), indicating an urgent need for more adaptive and engaging teaching materials. This study employs a Research and Development approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data were collected through observation, questionnaires, and documentation. Validation of materials, language, and media utilized a Likert scale ranging from 1 (very poor) to 5 (very good). Validation results from material experts, linguists, and media experts demonstrated excellent quality, with scores of 99.25%, 97.5%, and 89.14%, respectively. These findings indicate that the developed muhadatsah teaching materials possess a high level of quality in content, language, and media, making them highly suitable for beginner-level learners aiming to improve their Arabic speaking proficiency. Additionally, this study contributes innovative resources for educators, promoting more interactive and effective learning experiences that enhance learners’ confidence and speaking abilities in Arabic.